A 27-year retrospective clinical analysis of 2640 orthognathic surgery cases in the Tokyo Dental College. Issue 5 (September 2019) - Hamada, Yuji; Sugahara, Keisuke; Yoshida, Syuji; Watanabe, Akira; Bessho, Hiroki; Kasahara, Kiyohiro; Takano, Masayuki; Saito, Chikara; Shibahara, Takahiko; Katakura, Akira
Abstract: In this retrospective study, we aimed to analyze 2640 cases of orthognathic surgery performed in the Department of Oral and Maxillofacial Surgery, Tokyo Dental College, Suidobashi Hospital between April 1990 and March 2017. We also, analyzed the incidence of bad splits in bilateral sagittal split osteotomy (BSSRO) and massive blood loss exceeding 1000 g, between January 2012 and December 2016.The aim was to gain insight into the circumstances surrounding orthognathic surgery cases and to identify potential trends in jaw deformity treatment. The study included 952 males (35.9%) and 1688 females (64.1%). The majority of patients were 10–30 years old. Mandibular osteotomy was performed in 1820 and double-jaw surgery was performed in 787 cases, including the Le Fort I osteotomy and bilateral sagittal splitting ramus osteotomy (BSSRO). The annual number of orthognathic surgeries increased gradually, while the average operating time and blood loss decreased. Massive blood loss occurred in three cases, and bad splits following BSSRO were occurred in 13 cases between January 2012 and December 2016.There was a significant correlation between operating time and blood loss; operating times and blood loss improved over the 27-year study period.